Model of Pulsed Electrical Discharge Machining (EDM) using RL Circuit - Ade Erawan Bin Minhat; Nor Hisham Bin Hj Khamis; Azli Bin Yahya; Trias Andromeda; Kartiko Nugroho (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
This article presents a model of pulsed Electrical Discharge Machining (EDM) using RL circuit. There are several mathematical models have been successfully developed based on the initial, ignition and discharge phase of current and voltage gap. According to these models, the circuit schematic of transistor pulse power generator has been designed using electrical model in Matlab Simulink software to identify the profile of voltage and current during machining process. Then, the simulation results are compared with the experimental results.DOI: http://dx.doi.org/10.11591/ijpeds.v5i2.6681